2022
DOI: 10.1097/md.0000000000029077
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life and activities of daily living among elderly patients with hypertension and impaired physical mobility in home health care by antihypertensive drugs plus acupuncture

Abstract: Background: To evaluate the efficacy of acupuncture in improving quality of life (QOL) and activities of daily living among elderly patients with hypertension and impaired physical mobility in home health care.Methods: Seventy participants were allocated randomly to receive either acupuncture together with antihypertensive drugs (n = 35) or antihypertensive drugs only (n = 35). Acupuncture was conducted twice a week for 12 consecutive weeks, each lasting 30 minutes. Acupuncture points San Yin Jiao, Xue Hai, Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Particularly in low-and middle-economy countries such as China, Brazil, India and Mexico, where the economic burden of LCA and HT together contribute to 50 % of the total number of economic estimates identified (2) In Latin American countries, the prevalence of hypertension is high, with the countries with the highest prevalence being Brazil with 25-35 %, Paraguay with 34 %, Chile with 33,7 %, Uruguay and Venezuela with 33 %; also, in Colombia by 25 % (3) It is estimated that, by 2025, the figure could increase to 60 % reaching a figure of 1 560 000 000 individuals globally (4) Health-related quality of life (HRQOL) is a concept commonly used in the subjective assessment of a patient's health that reflects the patient's physical, psychological, social and emotional well-being as it is closely related to Health-related quality of life (QoL) and can cause an impact on their health status. (5,6) However, hypertension negatively affects patient QoL especially in older people, who have more health care needs and are more likely to have worse HRQOL than healthy people (7,8) For hypertensive patients, risk factors originate in two ways, the non-modifiable ones that are age, sex and genetics, which are aspects that are already established in humans; on the other hand, there are modifiable ones related to the habits and behaviors adopted in the lifestyle, the 12 which are food, the consumption of harmful substances and sedentary lifestyle (9,10) Therefore, improving lifestyle, making healthy habits, adequate adherence to treatment and maintaining positive mental health will allow hypertensive patients to avoid or reduce risk factors that may have consequences on their health well-being (11,12) In a study conducted in Poland, with participants between the ages of 30 to 89 years, they stated in their results that, the Health-related quality of life of people who were mostly men had a medium and good Healthrelated quality of life, concluding that healthy behaviors, follow the treatment properly and periodically take their blood pressure, towards keeping people's Health-related quality of life healthy (13) In a study conducted in Pakistan, with 384 hypertensive participants, they observed in their results that, most of the participants were male, 56 % of them had a poor Health-related quality of life related to health between the ages of 41 to 50 years, concluding that by not making healthy habits for the management of their disease, tended to have an inadequate Health-related quality of life (14) In a study carried out in Angola, with 113 participants, they stated in their results that, with respect to hypertensive participants, 64,6 % of them had a regular Health-related quality of life and 35,4 % a poor Healthrelated quality of life, concluding that the conditions and difficulty in accessing health services aggravate the disease due to factors such as overcrowding, inadequate feeding and poor living conditions (15) Therefore, the research objective is to determine the health-related quality of life in relation to health in hypertensive regular basic education teachers...…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in low-and middle-economy countries such as China, Brazil, India and Mexico, where the economic burden of LCA and HT together contribute to 50 % of the total number of economic estimates identified (2) In Latin American countries, the prevalence of hypertension is high, with the countries with the highest prevalence being Brazil with 25-35 %, Paraguay with 34 %, Chile with 33,7 %, Uruguay and Venezuela with 33 %; also, in Colombia by 25 % (3) It is estimated that, by 2025, the figure could increase to 60 % reaching a figure of 1 560 000 000 individuals globally (4) Health-related quality of life (HRQOL) is a concept commonly used in the subjective assessment of a patient's health that reflects the patient's physical, psychological, social and emotional well-being as it is closely related to Health-related quality of life (QoL) and can cause an impact on their health status. (5,6) However, hypertension negatively affects patient QoL especially in older people, who have more health care needs and are more likely to have worse HRQOL than healthy people (7,8) For hypertensive patients, risk factors originate in two ways, the non-modifiable ones that are age, sex and genetics, which are aspects that are already established in humans; on the other hand, there are modifiable ones related to the habits and behaviors adopted in the lifestyle, the 12 which are food, the consumption of harmful substances and sedentary lifestyle (9,10) Therefore, improving lifestyle, making healthy habits, adequate adherence to treatment and maintaining positive mental health will allow hypertensive patients to avoid or reduce risk factors that may have consequences on their health well-being (11,12) In a study conducted in Poland, with participants between the ages of 30 to 89 years, they stated in their results that, the Health-related quality of life of people who were mostly men had a medium and good Healthrelated quality of life, concluding that healthy behaviors, follow the treatment properly and periodically take their blood pressure, towards keeping people's Health-related quality of life healthy (13) In a study conducted in Pakistan, with 384 hypertensive participants, they observed in their results that, most of the participants were male, 56 % of them had a poor Health-related quality of life related to health between the ages of 41 to 50 years, concluding that by not making healthy habits for the management of their disease, tended to have an inadequate Health-related quality of life (14) In a study carried out in Angola, with 113 participants, they stated in their results that, with respect to hypertensive participants, 64,6 % of them had a regular Health-related quality of life and 35,4 % a poor Healthrelated quality of life, concluding that the conditions and difficulty in accessing health services aggravate the disease due to factors such as overcrowding, inadequate feeding and poor living conditions (15) Therefore, the research objective is to determine the health-related quality of life in relation to health in hypertensive regular basic education teachers...…”
Section: Introductionmentioning
confidence: 99%
“…(24,25,26,27,28,29,30,31) En un estudio realizado en Polonia, con participantes entre las edades de 30 a 89 años, manifestaron en sus resultados que, la calidad de vida de las personas que en su mayoría eran varones presentaban una calidad de vida media y buena, concluyendo que las conductas saludables, seguir el tratamiento adecuadamente y tomarse periódicamente su presión arterial, hacia que la calidad de vida de la persona se mantenga saludable. (32,33,34,35,36,37,38,39) En un estudio realizado en Pakistán, con 384 participantes hipertensos, observaron en sus resultados que, la mayoría de los participantes eran del sexo masculino, el 56 % de ellos tuvo una mala calidad de vida relacionada en la salud entre las edades de 41 a 50 años, concluyendo que al no realizar hábitos saludables para el manejo de su enfermedad, tendían presentar una calidad de vida inadecuada. (40,41,42,43) En un estudio realizado en Angola, con 113 participantes, manifestaron en sus resultados que, con respecto a los participantes hipertensos el 64,6 % de ellos tenían una calidad de vida regular y el 35,4 % una calidad de vida mala, concluyendo que las condiciones y la dificultad para acceder a los servicios de salud, agravan la enfermedad por factores como hacinamiento, alimentación inadecuadas y condiciones de vida malas.…”
Section: Introductionunclassified